Penggunaan Digital Story Telling dalam Pengajaran Speaking di SMPN 21 Mataram - Rahmawati , Lela; Sutarman; Aryani, R. Ayu Ida; Ayatullah, Rangga (Insan Kreasi Media, 2023)
A language proficiency must have been learnt or taught since early ages and speaking skills are the prominent to conquer the global world as it is a main means of communication. Digital Story Telling was conducted by using English training in SMPN 21 Mataram by teaching the students with the use of Participatory Action Research. The steps in this design are Planning, acting, observing, and reflecting. The results of an English Learning program showed that students' speaking abilities had improved in a number of areas, including confidence, fluency, pronunciation, grammar, and vocabulary. A range of speaking exercises, such as oral presentations, voice recordings, group discussions, and interviews, helped to strengthen those areas. Moreover, the mean gain of the students’ post-test was higher than the mean gain of the students’ pre-test. In the pre-test, the mean gain was 56.37; however, the students could achieve 74.05 in the post-test. In addition, students’ learning motivation increased in terms of: students involve in learning process, students solve the problem and search the issue, students try to work harder to avoid the failure.